Overseas Temples and Tamil Migratory Space - Pierre-Yves Trouillet (South Asia Multidisciplinary Academic Journal)
Temples have been places of major importance for Tamil societies for more than fifteen centuries. Following the migration of Tamilians from South India, the perpetuation overseas of their tradition as temple builders and the creation of a Tamil diaspora, they can now be found on the five continents. They are indicative of the exportation of Tamil Hinduism on a global scale and prompt us to ponder the relationships linking these overseas temples and the Tamil migratory space. This paper examines the identity issues as well as the spatial meanings and transnational connections related to the making of such places. The study of some of these temples in Canada and Mauritius helps to determine how Tamil temples have become major centres of transnational social spaces and to document the geographical features of the building of ‘hauts lieux’ by migrant communities in host countries.